Implementasi Bahasa Indonesia Dalam Penyampaian Kebijakan Informasi Publik - Dwi Nanda Cahya; Agastya, Difi Trenawindu; Agustin Dwi Setyowati; Alinda Rana Permata; Jesslyn Olyvviane; Natalia Desy Anggraeni (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2024)
ABSTRACT This research is motivated to convey policy information to the public so that they understand what the government wants to do for the community, with the delivery of good information that can be followed by the community to be implemented in life. The method used is a qualitative approach that is an explanation of the topic the author discusses. The author explains several references to qualitative research methods, Research & Development. The purpose of this research is to find out that Bahasa Indonesia can convey policy information to the public, understand what positive impacts will be obtained if conveying policy information to the public using Bahasa Indonesia, and find out the effectiveness of Bahasa Indonesia to convey policy information to the public properly. Keywords : Delivery of Information; Public Policy; Implementation of Life.